254 Neonatal Blood Transfusion-Can we make it Safer?. (October 2012) - Funston, LA; Hogan, M
Abstract : Background and Aims: A specific blood transfusion booklet was implemented in the Southern Health and Social Care Trust in 2010 for babies less than four months of age. This aimed to provide a standardised approach to blood transfusion documentation, highlighting indication for blood transfusion, consent and desired outcome achieved. Our aim with this audit was to assess completion of the blood booklet and identify areas for improvement. Method: A retrospective audit of the completion of the blood transfusion booklet within the neonatal unit in Craigavon Area Hospital was carried out. This was for all blood transfusions between October and December 2010. Results: 9 babies and 11 transfusion episodes were included. 3/9 babies were 25–30 weeks gestation, 4/9 babies were 1001–1500g. 4 of the transfusion episodes were classified as emergency transfusions. 1 adverse incident occurred during the audit period. Clinical observations were documented in 11 cases, consent in 9/11 cases. The main concerns were regarding blood prescription as special requirements, volume of blood and rate of transfusion were not documented adequately. Conclusion: This highlighted a need to improve the prescribing of blood products. The prescription chart was revised to include a column for volume and duration of transfusion in millilitres/hour. A specific blood transfusion booklet provides a readily available record of transfusions given and clear guidance for indication and prescribing of blood products. Our hope is that this will consequently result in safer blood transfusion practice.